Diversity of Ectomycorrhizal Fungi Associated with Eucalyptus in Africa and Madagascar. (21st November 2012) - Ducousso, Marc; Duponnois, Robin; Thoen, Daniel; Prin, Yves
Abstract : Use of the Australian genus Eucalyptus in short rotation plantations in Africa and Madagascar has developed over the last century to such an extent that it is becoming the most frequently planted genus in Africa. In order to find ecologically well-adapted eucalypts, foresters have tested different species of various origins and the number of tested Eucalyptus species now exceeds 150 in Africa. Due to the ability of eucalypts to naturally form ectomycorrhizae, even in the absence of any controlled introduction of compatible ectomycorrhizal fungal partners, their introduction in new ecosystems has direct consequences for ectomycorrhizal fungus communities. A bibliographical compilation, together with original field observations on putative ectomycorrhizal fungi associated with eucalypts in Africa and in Madagascar, has been drawn up in two lists: one for Africa and one for Madagascar where surprisingly high fungal diversity was observed. The level of diversity, the putative origin of the fungi, and their potential impact on native ectomycorrhizal fungi are discussed. The development of eucalypts plantations will inexorably lead to the increase of exotic fungal species being potentially invasive in the considered region.